2017
DOI: 10.1080/10826084.2016.1245745
|View full text |Cite
|
Sign up to set email alerts
|

Association of Suicide Attempts and Non-Suicidal Self-Injury Behaviors With Substance Use and Family Characteristics Among Children and Adolescents Seeking Treatment for Substance Use Disorder

Abstract: The prevalence of NSSI and HSA behaviors among substance using youth in our sample were 52% and 21% respectively. Cannabis and cocaine use was found to be a significant risk factor for HSA, and polysubstance use was associated with both NSSI and HSA. Parental separation/divorce, parental mental disorders, alcohol and drug use, and crime were the risk factors for HSA. A positive history of physical and sexual abuse increased the risk of HAS, and a history of neglect increased the risk of NSSI. Conclusions/impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 36 publications
4
39
0
1
Order By: Relevance
“…Wan and colleagues ( 34 ) demonstrated that a continuous experience of abuse was significantly associated with NSSI, independently of gender. More recently, Guvendeger Doksat et al ( 14 ) found that a history of neglect significantly increased the risk of NSSI, whereas physical/sexual abuse increased the odds of suicide attempts. Finally, Vaughn et al ( 35 ) found that, in a nationally representative sample including subjects who engaged in NSSI, the severity of CM was related to clinical psychiatric and personality disorders.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wan and colleagues ( 34 ) demonstrated that a continuous experience of abuse was significantly associated with NSSI, independently of gender. More recently, Guvendeger Doksat et al ( 14 ) found that a history of neglect significantly increased the risk of NSSI, whereas physical/sexual abuse increased the odds of suicide attempts. Finally, Vaughn et al ( 35 ) found that, in a nationally representative sample including subjects who engaged in NSSI, the severity of CM was related to clinical psychiatric and personality disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, when compared to males, females who experienced childhood traumatic experiences (particularly sexual abuse) ( 13 , 21 ) were more vulnerable to NSSI and suicidal behaviors. However, when physical and sexual abuse co-occurred ( 37 ) or when the experience of abuse was continuous ( 14 ), both males and females were at risk of NSSI and suicidal behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-injury behavior is a negative way for individuals to deal with current problems ( Sornberger et al, 2013 ), and causes great harm to adolescents’ mental health ( Guvendeger et al, 2017 ; Baetens et al, 2019 ). At the same time, self-injury behavior is also a risk factor leading to suicide.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the frequency or severity of self-injurious behavior is considered as a useful indicator of injury (Gratz, 2001; Prinstein, 2008), but Feng (2008) suggested that the overall level of self-injury was a comprehensive indicator that fully considered the frequency and severity of injury to the body, which more accurately reflects the self-injury state of adolescents. Many studies have found that self-injury is associated with numerous psychological disorders (Selby et al, 2012; Doksat et al, 2017) and predicts future suicidal intention and behavior (Guan et al, 2012; Klonsky et al, 2013).…”
Section: Introductionmentioning
confidence: 99%